2020
DOI: 10.5114/pjp.2020.95412
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis discloses differences in nuclear parameters between ERG+ and ERG– prostatic carcinomas

Abstract: Prostatic carcinoma (PC) is the most frequent urologic cancer and one of the most frequent cancers in males; it is a heterogeneous disease, in terms of molecular features, morphology and prognosis. About half of cases depends on TMPRSS2-ETS translocation which leads to a production of ERG transcription factor. ERG+ and ERG-cancers seem to differ in a number of features, which could lead to an altered nuclear structure; the aim of the study was to test this hypothesis. The material consisted of total 39 PC case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A recent analysis by Alshalalfa et al showed the highest risk for uncurable disease in patients with low NPY and ERG-positive subgroup (74). The TMPRSS2-ERG fusion is an early and one of the most common genetic abnormalities responsible for tumor invasion and progression affecting growth pathways and regulating differentiation, cell cycle, proliferation, angiogenesis and morphology in PCa (78)(79)(80). The overexpression of ERG is a biomarker of fusion, and may be related to unfavorable prognostic factors and decreased survival (80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis by Alshalalfa et al showed the highest risk for uncurable disease in patients with low NPY and ERG-positive subgroup (74). The TMPRSS2-ERG fusion is an early and one of the most common genetic abnormalities responsible for tumor invasion and progression affecting growth pathways and regulating differentiation, cell cycle, proliferation, angiogenesis and morphology in PCa (78)(79)(80). The overexpression of ERG is a biomarker of fusion, and may be related to unfavorable prognostic factors and decreased survival (80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%